How do novel seat positions impact usability of child restraints?. (June 2021) - Tremoulet, Patrice D.; Belwadi, Aditya; Corr, Brendan; Sarfare, Shreyas; Seacrist, Tom; Tushak, Sophia
Highlights: Novel seating configurations may impact family use of autonomous vehicles. "Living room-style" seating can make it harder to use child restraint systems. Parents & children like facing one another, but also like to face frontwards. Abstract: Autonomous driving technology and changes in regulations may create an environment that allows novel vehicle interiors. It is important to consider impact on all types of passengers when contemplating interior design, particularly for vehicles that may be used by families with children. We developed a fixture that enables us to change the orientation of each of 4 car seats and used it to simulate three different vehicle interiors. Ten families with children aged 3 months to 7 years interacted with each of the simulated interiors as part of a usability study. Times to install and remove child restraint systems were not significantly different across the three simulated vehicle interiors, but parents were able to release children fastest when using the "X" configuration, which had all seats on a diagonal facing the middle of the vehicle. While overall experience ratings didn't differ significantly, seven out of ten parents indicated that they liked the "X" configuration better than the other two configurations tested. Reasons included: ability to interact with other passengers, ability to see the road, and legroom/comfort. However, many participants disliked having some passengers not facing forward. Overall, parents liked facing their children, but several said that they would only be comfortable if they could see out of the front windshield; meanwhile, children liked seeing their parents' faces but also preferred to face forward. Child restraint system and vehicle manufacturers could benefit from considering this study when designing new products.